THE ROLE OF CELL ADHESION TO BIOMATERIAL - Yenny Yustisia (Fakultas Kedokteran Gigi Universitas Jember, 2011)
The efficacy of biomaterials-either as replacements for damaged tissues, or as a temporary scaffolds for the manufacture of engineered tissues and organs- relies on the ability of the material surface to regulate cell adhesion. Adhesion plays a critical role to regulate proliferation, differentiation and phenotypic behaviour, therefore consequently impact tissue development and function. Cell adhesion to biomaterials may be characterized in terms of specific and nonspecific interactions. Specific interaction entail cell receptor recognition, whereas nonspecific interaction encompass noncovalent attractive forces. This paper gives a review of the phenomena occuring in cell/material interaction and particularly the role of cell adhesion